Subverting Gendered Identities in Faiqa Mansab’s This House of Clay and Water: A Post-Feminist Study - Iqbal, Javed; Ayaz, Zainab; Riffat, Hafiz Adnan (Pakistan Languages and Humanities Review, 2025)
The present study is aimed to explicate the space for gender with assumption that how gendered identities are subverted. This research has analyzed Faiqa Mansab’s This House of Clay and Water by drawing on Nicola Rivers’ Postfeminism(s) and The Arrival of Fourth Wave: Turning Tides. The data was selected in the form of extracts from the different parts of the novel and were analyzed accordingly. It concerns neither with feministic nor misogynistic perspective but to repatriate a balance in genders, deteriorated by the subversion of identities. The significance of the study lies in the fact of urgency to redefine the gendered boundaries in the present societies. The chief objective of the present attempt was to assess the imbalance of space and subversion of identities for all genders. It also considers the pseudo feminists’ portrayal of women as vulnerable subject under observation. The basic concern of the present attempt was to evaluate the imbalance of space and subversion of identities in the present era. The results and discussions have rendered the mitigation of imbalance in genders articulated in Faiqa Mansab’s This House of Clay and Water.